PSYCHODIAGNOSTICS − ONE OF THE TOOLS OF AIRCRAFT CREW RESOURCE MANAGEMENT - O. V. Arinicheva; A. V. Malishevskiy (Научный вестник МГТУ ГА)
This article is devoted to a question of the perfection of psychodiagnostic techniques, as tool of aircraft crew resource management. First of all, article is devoted to increase of the validity of the socionic tests.